2021
DOI: 10.1111/jfb.14864
|View full text |Cite
|
Sign up to set email alerts
|

Eating catch of the day: the diet of porbeagle shark Lamna nasus (Bonnaterre 1788) based on stomach content analysis, and the interaction with trawl fisheries in the south‐western Atlantic (52° S–56° S)

Abstract: This work examined the diet of the porbeagle shark Lamna nasus in the south‐west Atlantic Ocean (SWAO, Argentina, 52° S–56° S) by analysing the stomach content information obtained by scientific observers who sampled specimens captured as by‐catch on‐board commercial fishing vessels from 2010 to 2020. A total of 148 fishing sites were analysed, in which the estimated catch was composed mainly of hoki Macruronus magellanicus (56.00%) and southern blue whiting Micromesistius australis (33.13%). From 413 porbeagl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 67 publications
(96 reference statements)
0
3
0
Order By: Relevance
“…More specifically, blue sharks with epipelagic feeding habits, a diet dominated especially by cephalopods [ 43 ], exhibited lower THg accumulation than other shark species, that because of their relationship with seafloor sediments showed more significant levels (e.g., picked dogfish: 1.25 μg g −1 w.w., smooth hound: 1.03 μg g −1 w.w.). Porbeagle, also an epipelagic shark species but with a strictly carnivore feeding pattern [ 44 ], presented higher values than blue sharks. These findings further support the aforesaid and are in accordance with previous studies on Hg accumulation in fish, confirming the well-known fact that Hg concentration is heavily controlled by feeding habits and habitat [ 45 , 46 ].…”
Section: Resultsmentioning
confidence: 99%
“…More specifically, blue sharks with epipelagic feeding habits, a diet dominated especially by cephalopods [ 43 ], exhibited lower THg accumulation than other shark species, that because of their relationship with seafloor sediments showed more significant levels (e.g., picked dogfish: 1.25 μg g −1 w.w., smooth hound: 1.03 μg g −1 w.w.). Porbeagle, also an epipelagic shark species but with a strictly carnivore feeding pattern [ 44 ], presented higher values than blue sharks. These findings further support the aforesaid and are in accordance with previous studies on Hg accumulation in fish, confirming the well-known fact that Hg concentration is heavily controlled by feeding habits and habitat [ 45 , 46 ].…”
Section: Resultsmentioning
confidence: 99%
“…In addition to competition for access to food resources, females in the austral Atlantic zone have access to prey with high-fat content, such as hoki M. magellanicus and southern blue whiting M. australis (Massa et al, 2018). Thus, the identification of the austral zone of the Southwest Atlantic Ocean as a critical feeding area (Belleggia et al, 2021) suggests that the costs associated with migrating to colder waters would outweigh the investment in reproduction (ovarian and embryonic development) due to the access to prey with high-energy content and the low cost of searching for optimal foraging areas (without interspecific competition), allowing for the maximization of intake and assimilation necessary to maintain endothermy (Bernal et al, 2012). F I G U R E 6 Monthly variation in the mean fork length (L F , cm) of porbeagle Lamna nasus embryos caught in the austral region of the southwestern Atlantic Ocean.…”
Section: Discussionmentioning
confidence: 99%
“…More recently, using traditional stomach content analysis of porbeagles caught by trawl fisheries (freezers, factories, and ice-chilled vessels), Belleggia et al (2021) found that these sharks feed on hoki (Macruronus magellanicus) and southern blue whiting (Micromesistius australis) and additionally that the low percentage of empty stomachs would suggest that this region is a critical feeding area. In addition to these puzzle pieces, there is a lack of reproductive knowledge regarding maturity, litter size, and reproductive cycle.…”
Section: Introductionmentioning
confidence: 99%
“…Porbeagle sharks can reach a large body size and perform long seasonal movements [2,3]. Lamna nasus mainly feeds on small pelagic fishes and cephalopods [4] although its feeding behavior is considered opportunistic because its diet varies among regions [5,6]. Since the 1930s, porbeagle sharks were subject to commercial fisheries that resulted in a severe decrease in their North Atlantic populations [7,8].…”
Section: Introductionmentioning
confidence: 99%